A water-free high-nickel ternary positive electrode material and its preparation method and application

Through the water-free spray coating technology, a uniform oxide and salt compound coating layer is formed on the surface of the high-nickel ternary positive electrode material, which solves the problem of easy breakage and capacity reduction in the material during charging and discharge, and improves the capacity, rate performance and cycle life of the material.

CN115188950BActive Publication Date: 2025-04-25NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210869751.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-21
Publication Date
2025-04-25
Estimated Expiration
2042-07-21

AI Technical Summary

Technical Problem

The high-nickel ternary cathode material is prone to shatter and powder during charging and discharging, resulting in material failure. The increase in nickel content leads to an increase in ionic impedance, and the decomposition effect of the material surface on the electrolyte is enhanced. The existing wet co-precipitation coating method causes the surface Li2O to be washed away due to water washing, and the material capacity is reduced.

Method used

Using a water-free spray coating method, the surface of high-nickel ternary cathode material is neutralized by acid-base neutralization reaction to form hydroxides or salts, and is converted into oxides and salt compounds at high temperatures to form a uniform Al2O3 and other salt compounds coating layer, avoiding the damage to the surface structure by water washing.

Benefits of technology

It improves the capacity and rate performance of the cathode material, reduces electrochemical impedance (DCR), extends the material's cycle life, and reduces wastewater treatment costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115188950B_ABST
    Figure CN115188950B_ABST
Patent Text Reader

Abstract

The present invention discloses a water-free high-nickel ternary positive electrode material and a preparation method and application thereof. The molecular formula of the positive electrode material is: LiNi a Co b Mn c O2 / N, wherein 0.7≤a<1, 0<b<0.2, 0<c<0.2, a+b+c=1, N is a coating layer, and the coating layer is formed by one or more of SiO2, CoO2, Al2O3, ZrO2, SrO, Li3PO4, and AlPO4. The beneficial effects of the present invention are as follows: the water-free high-nickel ternary positive electrode material of the present invention reacts on the surface of the material by spraying to generate hydroxides or salts, which are converted into oxides and salt compounds at high temperature, thereby coating a layer of Al2O3 and other salt compounds on the surface, the coating layer is uniform, and no water washing is required, the capacity of the material is improved, the rate performance is better, the DCR is lower, the wastewater treatment caused by the water washing process is avoided, the cost of the material is reduced, the material has a higher gram capacity, a longer cycle life, the rate performance is improved, and the material performance is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery preparation, and in particular relates to a water-free high-nickel ternary positive electrode material and a preparation method and application thereof. Background Art

[0002] Due to the environmental pollution problem of fuel vehicles, electric vehicles are becoming more and more popular among people. Especially in recent years, various countries have set timelines for banning the sale of fuel vehicles and oil prices have risen sharply, making electric vehicles the first choice for people to buy cars. In order to meet the range, ternary materials are the best choice, but low-nickel materials are more expensive. High-nickel materials have become the preferred materials for battery manufacturers, especially Ni83 and Ni90 materials that have gradually matured in recent years, and some material manufacturers have even launched Ni95 materials.

[0003] The increase in nickel content leads to an increase in the ionic impedance of the material. As the nickel content increases, the crystal volume changes greatly during the charge and discharge process, making the crystal easily broken and pulverized due to long-term stress changes, leading to material failure. At the same time, as the nickel content increases, the decomposition effect of the material surface on the electrolyte is enhanced. In order to solve these problems of high-nickel materials, many researchers use internal doping of metal elements to stabilize the lattice and external coating of inert materials to reduce the contact between the electrolyte and the material surface. However, if the dry coating layer is thin, it cannot cover the surface. If it covers the surface, the coating layer is too thick, so that the material cycle performance cannot play the best cycle characteristics. Some people have proposed wet co-precipitation coating. Although it can be coated well, the Li2O with lithium replenishment function on the surface is washed away after water washing, resulting in a decrease in the capacity of the material. Summary of the invention

[0004] The object of the present invention is to provide a water-free high-nickel ternary positive electrode material having a coating layer equivalent to that of wet coating, avoiding the damage to the surface structure caused by water washing, improving the capacity and rate performance of the positive electrode material, and avoiding the wastewater treatment caused by the water washing process, as well as a preparation method and application thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A water-free high-nickel ternary positive electrode material, the molecular formula of the positive electrode material is: LiNi a Co b Mn c O2 / N, wherein 0.7≤a<1, 0<b<0.2, 0<c<0.2, a+b+c=1, N is a coating layer, and the coating layer is formed by one or more of SiO2, CoO2, Al2O3, ZrO2, SrO, Li3PO4, AlPO4, and the free Li of the positive electrode material + Content: Free Li +Content ≤2000ppm.

[0007] The above-mentioned water-free high-nickel ternary positive electrode material, as a preferred implementation scheme, the Li2CO3 content of the positive electrode material is: Li2CO3 content ≤ 500ppm, and the LiOH content of the positive electrode material is: 2000 ≤ LiOH content ≤ 5000ppm.

[0008] The above-mentioned water-free high-nickel ternary positive electrode material, as a preferred embodiment, has a BET range of: 0.2-1.0 m 2 / g, the tap density of the positive electrode material is: 2.3g / cm 3 ~3.0g / cm 3 .

[0009] In a second aspect of the present application, a method for preparing a water-free high-nickel ternary positive electrode material is provided, comprising the following steps:

[0010] (1) mixing the precursor and the lithium source uniformly and sintering at high temperature to obtain a sintered material;

[0011] (2) Spraying a Li-containing + The alkaline solution is then sprayed with an acidic salt solution, and after the spraying is completed, the solution is dried and sintered to obtain the water-free high-nickel ternary positive electrode material.

[0012] The above-mentioned method for preparing a water-free high-nickel ternary positive electrode material is, as a preferred embodiment, in step (1), the molecular formula of the precursor is: Ni a Co b Mn c (OH)2, wherein a≥0.7, and a+b+c=1; the lithium source is one or more of LiOH, Li2CO3, LiNO3, and CH3COOLi; the molar ratio of the precursor to the lithium source is 0.8-1.2:1.

[0013] The above-mentioned method for preparing a water-free high-nickel ternary positive electrode material is, as a preferred embodiment, the Li-containing + The alkaline solution is a LiAlO2 solution or a Li2SiO3 solution. + In alkaline solution, Li + The concentration is 0.1-1 mol / L, and the spraying rate of the Li alkaline solution is 0.1-1 L / min. The LiAlO2 solution or Li2SiO3 solution contacts the acidic salt solution to undergo a neutralization reaction to form Al(OH)3 and other salts uniformly attached to the surface of the calcined material.

[0014] The above-mentioned method for preparing a water-free high-nickel ternary positive electrode material is, as a preferred embodiment, the acidic salt solution is Co(NO3)2, Zr(NO3)4, Zr(SO4)4, Sr(NO3)2, HF, LiF, LiH2PO4 or Al(H2PO3)3, the pH of the acidic salt solution is 1-6, and the spraying rate of the acidic salt solution is 0.1~1mol / L.

[0015] The above-mentioned method for preparing a water-free high-nickel ternary positive electrode material is, as a preferred embodiment, the Li-containing + The molar ratio of the spraying amount of the alkaline solution to the acidic salt solution is 0.1 to 5:1, and the Li-containing + The spray amount of the alkaline solution is 500 to 15000 ppm.

[0016] The above-mentioned method for preparing a water-free high-nickel ternary positive electrode material is a preferred embodiment. In step (2), the drying is vacuum drying, and the sintering is first heated to 300-350°C at a heating rate of 1-10°C / min, kept warm for 1-15h, then cooled to 180-220°C at a cooling rate of 1-3°C / min, and finally cooled to room temperature with the furnace.

[0017] In a third aspect of the present application, a lithium battery is provided, which comprises the above-mentioned water-free high-nickel ternary positive electrode material or the positive electrode material prepared by the above-mentioned method.

[0018] The beneficial effects of the present invention are as follows: the BET range of the water-free high-nickel ternary positive electrode material of the present invention is 0.2 to 1.0 m 2 / g, tap density is 2.3g / cm 3 Above, Li2CO3 content ≤ 500ppm, LiOH content ≤ 5000ppm, free Li + The content is ≤2000ppm; the positive electrode material of the present invention has good rate performance and lower DCR.

[0019] The 800mAh battery cell is discharged at 4C current for 30S under the specified SOC% state, and the current value and the voltage difference before and after discharge are recorded. The ratio of the voltage difference to the discharge current is the DCR value under the SOC state. The DCR range of 10% state of charge is 220mΩ~240mΩ, the DCR range of 20% state of charge is 125mΩ~140mΩ, the DCR range of 50% state of charge is 80mΩ~90mΩ, the DCR range of 90% state of charge is 85mΩ~100mΩ, and the DCR range of 100% state of charge is 85mΩ~100mΩ.

[0020] The water-free high-nickel ternary positive electrode material of the present invention generates hydroxides or salts through acid-base neutralization reaction on the surface of the material by spraying, and is converted into oxides and salt compounds through high temperature, so as to coat a layer of Al2O3 and other salt compounds on the surface. The coating layer is uniform and does not need to be washed with water, so the capacity of the material is improved. At the same time, due to the thinner coating layer, the rate performance of the material is better and the DCR is lower, which avoids the wastewater treatment caused by the water washing process and reduces the cost of the material. The material has a higher gram capacity, a longer cycle life, and the rate performance is improved, and the material performance is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0022] The structures, proportions, sizes, etc. illustrated in this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with the technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantial technical significance. Any structural modification, change in proportion or adjustment of size shall still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.

[0023] Figure 1 This is a graph of the capacity retention rate of a 45°C cycle provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be described clearly and completely in combination with examples. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.

[0025] The present invention describes a water-free high-nickel ternary positive electrode material, the molecular formula of the positive electrode material is: LiNi a Co b Mn cO2 / N, wherein 0.7≤a<1, 0<b<0.2, 0<c<0.2, a+b+c=1, N is a coating layer, and the coating layer is formed by one or more of SiO2, CoO2, Al2O3, ZrO2, SrO, Li3PO4, AlPO4, and the free Li of the positive electrode material + Content: Free Li + Content ≤2000ppm.

[0026] The 0.1C gram capacity of the positive electrode material of the present invention is ≥210 mAh, the Li2CO3 content of the positive electrode material is: Li2CO3 content ≤500 ppm, and the LiOH content of the positive electrode material is: 2000≤LiOH content≤5000 ppm.

[0027] The BET range of the positive electrode material described in the present invention is: 0.2~1.0m 2 / g, the tap density of the positive electrode material is: 2.3-3.0g / cm 3 .

[0028] The preparation method of the water-free high-nickel ternary positive electrode material of the present invention is:

[0029] (1) Polycrystalline precursor: Ni a Co b Mn c (OH)2, wherein a≥0.7, and a+b+c=1, is uniformly mixed with a lithium source in a molar ratio of 0.8-1.2:1, preferably 0.95-1.05:1. The lithium source may be one or more of LiOH, Li2CO3, LiNO3, and CH3COOLi.

[0030] (2) Pass the mixture through a 200-400 mesh sieve and place it into a sagger.

[0031] The obtained mixture is treated with the following three-stage sintering process: first, the temperature is increased to 300-500°C at a heating rate of 1-10°C / min, and the temperature is kept for 2-10 hours; then the temperature is increased to 500-600°C at a heating rate of 1-10°C / min, and the temperature is kept for 1-2 hours; then the temperature is increased to 700-800°C at a heating rate of 1-10°C / min, and the temperature is kept for 1-20 hours, and then the furnace is cooled to room temperature; during the sintering process, the oxygen concentration needs to be maintained between 85% and 100%, and the fired material is crushed for standby use.

[0032] (3) Prepare an alkaline solution containing lithium ions (containing Li +The alkaline solution is LiAlO2 solution or Li2SiO3 solution), and an acidic salt solution with a pH of 1-6 (Co(NO3)2, Zr(NO3)4, Zr(SO4)2, Sr(NO3)2, HF, LiF, LiH2PO4 or Al(H2PO3)3) is prepared and set aside.

[0033] (4) The polycrystalline material after the primary sintering is crushed and screened, and then loaded into a high-speed mixer, and the speed is controlled at 1000-4000 r / min, preferably 2000-3000 r / min; the alkaline solution containing lithium ions is sprayed onto the material after the primary sintering through a spray device, and the spray rate is 0.1L-1L / min, preferably 0.2-0.5L / min; after the spraying is completed, the acidic salt solution is sprayed onto the particle surface, and the spray rate is 0.1L-1L / min. + The molar ratio of the spraying amount of the alkaline solution to the acidic salt solution is 0.1 to 5:1. After being fully mixed, the mixture is dried at a drying temperature of 20 to 500° C., preferably 120 to 240° C.

[0034] (5) The high-nickel ternary material obtained in step (4) is sintered again: the temperature is increased to 300-350°C at a heating rate of 1-10°C / min, kept at this temperature for 1-15h, then decreased to 180-220°C at a cooling rate of 1-3°C / min, and finally cooled to room temperature in the furnace to obtain a water-free positive electrode high-nickel ternary material.

[0035] Example 1

[0036] The method for preparing the water-free high-nickel ternary positive electrode material described in Example 1 is as follows: 0.83 Co 0.12 Mn 0.05 (OH)2 and LiOH were mixed in a molar ratio of 1:1.02 and passed through a 200-400 mesh sieve. After sieving, the mixture was placed in a sagger.

[0037] The above mixture is treated by the following three-stage sintering process: first, the temperature is increased to 350°C at a heating rate of 5°C / min and kept at this temperature for 3 hours; then the temperature is increased to 550°C at a heating rate of 4°C / min and kept at this temperature for 2 hours; then the temperature is increased to 770°C at a heating rate of 2°C / min and kept at this temperature for 10 hours, and then the mixture is cooled to room temperature with the furnace; during the sintering process, the oxygen concentration needs to be maintained between 85% and 100%, and the fired material is crushed for later use.

[0038] The obtained calcined material is placed in a high-speed mixer at 2000r / min for dispersion, and a 0.4mol / L LiAlO2 solution is sprayed on the calcined material in the high-speed mixer at a spray rate of 0.3L / min. After spraying, a Co(NO3)2 solution with a pH of 2 is sprayed at a spray rate of 0.2L / min. The molar ratio of the spray solution is 2:1, and the spray amount of the alkaline solution (LiAlO2 solution) is 1500ppm. After spraying, the material is dried at a drying temperature of 180±5℃ for 5h. After drying, the material is loaded into a sagger for sintering. The sintering conditions are heating to 350℃ at a heating rate of 5℃ / min, O2 concentration ≥95%, keeping warm for 8h, then cooling to 200℃ at a cooling rate of 2℃ / min, and finally cooling to room temperature with the furnace to obtain a water-free high-nickel ternary positive electrode material.

[0039] The relevant chemical equation is: Co(NO3)2+2H2O=Co(OH)2+2HNO3

[0040] LiAlO2+2H2O=LiOH+Al(OH)3

[0041] LiOH+HNO3=H2O+LiNO3

[0042] 2Al(OH)3=Al2O3+3H2O

[0043] Example 2

[0044] The method for preparing the water-free high-nickel ternary positive electrode material described in Example 2 is as follows: 0.83 Co 0.12 Mn 0.05 (OH)2 and LiOH were mixed in a molar ratio of 1:1.02 and passed through a 200-400 mesh sieve. After sieving, the mixture was placed in a sagger.

[0045] The mixture was sintered in three stages: first, the temperature was increased to 350°C at a heating rate of 5°C / min and kept for 3 hours; then the temperature was increased to 550°C at a heating rate of 4°C / min and kept for 2 hours; then the temperature was increased to 770°C at a heating rate of 2°C / min and kept for 10 hours, and then the mixture was cooled to room temperature in the furnace; during the sintering process, the oxygen concentration needed to be maintained between 85% and 100%, and the fired material was crushed for later use.

[0046] The obtained calcined material is placed in a high-speed mixer at 2000r / min for dispersion, and a 0.5mol / L LiAlO2 solution is sprayed on the calcined material in the high-speed mixer at a spray rate of 0.3L / min. After spraying, a Co(NO3)2 solution with a pH of 4 is sprayed, the molar ratio of the spray solution is 2:1, and the spray amount of the alkaline solution (LiAlO2 solution) is 1500ppm. After spraying, the material is dried at a temperature of 180±5℃ for 5h. After drying, the material is loaded into a sagger for sintering. The sintering conditions are heating to 350℃ at a heating rate of 5℃ / min, O2 concentration ≥95%, keeping warm for 8h, then cooling to 200℃ at 2℃ / min, and finally cooling to room temperature with the furnace to obtain a water-free high-nickel ternary positive electrode material.

[0047] Chemical formula: Co(NO3)2+2H2O=Co(OH)2+2HNO3

[0048] LiAlO2+2H2O=LiOH+Al(OH)3

[0049] LiOH+HNO3=H2O+LiNO3

[0050] 2Al(OH)3=Al2O3+3H2O

[0051] Example 3

[0052] The method for preparing the water-free high-nickel ternary positive electrode material described in Example 3 is as follows: 0.83 Co 0.12 Mn 0.05 (OH)2 and LiOH were mixed in a molar ratio of 1:1.02 and passed through a 200-400 mesh sieve. After sieving, the mixture was placed in a sagger.

[0053] The mixture was sintered in two stages: first, the temperature was increased to 350°C at a heating rate of 5°C / min and kept for 3 hours; then the temperature was increased to 550°C at a heating rate of 4°C / min and kept for 2 hours; then the temperature was increased to 770°C at a heating rate of 2°C / min and kept for 10 hours, and then the mixture was cooled to room temperature in the furnace; during the sintering process, the oxygen concentration needed to be maintained between 85% and 100%, and the fired material was crushed for later use.

[0054] The obtained calcined material is placed in a high-speed mixer at 2000r / min for dispersion, and a 0.4mol / L LiAlO2 solution is sprayed on the calcined material in the high-speed mixer at a spray rate of 0.2L / min. After spraying, a Co(NO3)2 solution with a pH of 2 is sprayed at a spray rate of 0.2L / min. The molar ratio of the sprayed solution is 1:2, and the spray amount of the alkaline solution (LiAlO2 solution) is 750ppm. After spraying, the material is dried at a drying temperature of 180±5℃ for 5h. After drying, the material is loaded into a sagger for sintering. The sintering conditions are heating to 350℃ at a heating rate of 5℃ / min, O2 concentration ≥95%, keeping warm for 8h, then cooling to 200℃ at 2℃ / min, and finally cooling to room temperature with the furnace to obtain a water-free high-nickel ternary positive electrode material.

[0055] Chemical formula: Co(NO3)2+2H2O=Co(OH)2+2HNO3

[0056] LiAlO2+2H2O=LiOH+Al(OH)3

[0057] LiOH+HNO3=H2O+LiNO3

[0058] 2Al(OH)3=Al2O3+3H2O

[0059] Example 4

[0060] The method for preparing the water-free high-nickel ternary positive electrode material described in Example 4 is as follows: 0.83 Co 0.12 Mn 0.05 (OH)2 and LiOH were mixed in a molar ratio of 1:1.02 and passed through a 200-400 mesh sieve. After sieving, the mixture was placed in a sagger.

[0061] The mixture was sintered in two stages: first, the temperature was increased to 350°C at a heating rate of 5°C / min and kept for 3 hours; then the temperature was increased to 550°C at a heating rate of 4°C / min and kept for 2 hours; then the temperature was increased to 770°C at a heating rate of 2°C / min and kept for 10 hours, and then the mixture was cooled to room temperature in the furnace; during the sintering process, the oxygen concentration needed to be maintained between 85% and 100%, and the fired material was crushed for later use.

[0062] The obtained calcined material is placed in a high-speed mixer at 2000r / min for dispersion, and a 0.3mol / L Li2SiO3 solution is sprayed on the calcined material in the high-speed mixer at a spray rate of 0.2L / min. After spraying, a LiH2PO4 solution with a pH of 2 is sprayed, the molar ratio of the spray solution is 1:2, and the spray amount of the alkaline solution (Li2SiO3 solution) is 1200ppm. After spraying, the material is dried at a drying temperature of 150±5°C and a drying time of 6h. After the material is dried, it is loaded into a sagger for sintering. The sintering conditions are heating to 350°C at a heating rate of 5°C / min, O2 concentration ≥95%, keeping warm for 8h, then cooling to 200°C at a rate of 2°C / min, and finally cooling to room temperature with the furnace to obtain a water-free high-nickel ternary positive electrode material.

[0063] Chemical formula: Li2SiO3+2H2O=2LiOH+H2SiO3

[0064] LiH2PO4+LiOH=Li2HPO4+H2O

[0065] LiH2PO4+2LiOH=Li3PO4+2H2O

[0066] H2SiO3=H2O+SiO2

[0067] Example 5

[0068] The method for preparing the water-free high-nickel ternary positive electrode material described in Example 5 is as follows: 0.83 Co 0.12 Mn 0.05 (OH)2 and LiOH were mixed in a molar ratio of 1:1.02 and passed through a 200-400 mesh sieve. After sieving, the mixture was placed in a sagger.

[0069] The mixture was sintered in two stages: first, the temperature was increased to 350°C at a heating rate of 5°C / min and kept for 3 hours; then the temperature was increased to 550°C at a heating rate of 4°C / min and kept for 2 hours; then the temperature was increased to 770°C at a heating rate of 2°C / min and kept for 10 hours, and then the mixture was cooled to room temperature in the furnace; during the sintering process, the oxygen concentration needed to be maintained between 85% and 100%, and the fired material was crushed for later use.

[0070] The obtained calcined material is placed in a high-speed mixer at 2000r / min for dispersion, and a 0.3mol / L Li2SiO3 solution is sprayed on the calcined material in the high-speed mixer at a spray rate of 0.2L / min. After spraying, a Zr(NO3)4 solution with a pH of 2 is sprayed, the molar ratio of the spray solution is 1:1, and the spray amount of the alkaline solution (Li2SiO3 solution) is 800ppm. After spraying, the material is dried at a temperature of 170±5°C for 6h. After the material is dried, it is loaded into a sagger for sintering. The sintering conditions are heating to 350°C at a heating rate of 5°C / min, O2 concentration ≥95%, keeping warm for 8h, then cooling to 200°C at a rate of 2°C / min, and finally cooling to room temperature with the furnace to obtain a water-free high-nickel ternary positive electrode material.

[0071] Related chemical equation: Li2SiO3+2H2O=2LiOH+H2SiO3

[0072] Zr(NO3)4+4H2O=Zr(OH)4+4HNO3

[0073] LiOH+HNO3=H2O+LiNO3

[0074] H2SiO3=H2O+SiO2

[0075] Zr(OH)4=ZrO2+2H2O

[0076] Comparative Example 1

[0077] The difference between the high-nickel positive electrode material described in Comparative Example 1 and the water-free high-nickel ternary positive electrode material described in Example 1 is that:

[0078] The preparation method of the high-nickel positive electrode material described in Comparative Example 1 is as follows: a sintered material is mixed evenly with Al2O3 and CoO2, and then loaded into a sagger, wherein the Al2O3 content is 1500ppm, and the CoO2 content is 750ppm, and sintering is performed. The sintering conditions are heating to 350°C at a heating rate of 5°C / min, O2 concentration ≥95%, keeping warm for 8h, then cooling to 200°C at 2°C / min, and finally cooling to room temperature with the furnace to obtain a high-nickel ternary positive electrode material.

[0079] Comparative Example 2

[0080] The difference between the high nickel positive electrode material described in Comparative Example 2 and the water-free high nickel ternary positive electrode material described in Example 2 is that:

[0081] The preparation method of the high-nickel positive electrode material described in Comparative Example 2 is as follows: the calcined material: water = 100:1 is washed with water, and after the washing is completed, the material is filtered into a filter cake and dried, the drying temperature is 180±5°C, the drying time is 5h, and then mixed evenly with Al2O3 and CoO2 and loaded into a sagger, wherein the Al2O3 content is 1500ppm, and the CoO2 content is 750ppm, and sintering is carried out. The sintering conditions are heating to 350°C at a heating rate of 5°C / min, O2 concentration ≥95%, keeping warm for 8h, then cooling to 200°C at 2°C / min, and finally cooling to room temperature with the furnace to obtain a high-nickel ternary positive electrode material.

[0082] Comparative Example 3

[0083] The difference between the high nickel positive electrode material described in Comparative Example 3 and the water-free high nickel ternary positive electrode material described in Example 5 is that:

[0084] The preparation method of the high-nickel positive electrode material described in Comparative Example 3 is as follows: a calcined material: water = 100:1 is mixed, Li2SiO3 and Zr(NO3)4 are added to the mixed solution, wherein the addition amount of the two materials is 800ppm, and the mixture is stirred and mixed at 50r / min. After 40 minutes, the material is filtered into a filter cake and dried at a drying temperature of 170±5°C and a drying time of 6h. After the material is dried, it is loaded into a sagger and sintered. The sintering conditions are heating to 350°C at a heating rate of 5°C / min, O2 concentration ≥95%, keeping warm for 8h, then cooling to 200°C at 2°C / min, and finally cooling to room temperature with the furnace to obtain a water-free high-nickel ternary positive electrode material.

[0085] Comparative Example 4

[0086] The difference between the high nickel positive electrode material described in Comparative Example 4 and the water-free high nickel ternary positive electrode material described in Example 5 is that:

[0087] The preparation method of the high nickel positive electrode material described in Comparative Example 4 is:

[0088] The obtained calcined material is placed in a high-speed mixer at 2000r / min for dispersion, and 0.2mol / L Zr(NO3)4 solution is sprayed on the calcined material in the high-speed mixer at a spray rate of 0.2L / min, and the spray amount is 800ppm. After spraying, the material is dried at a drying temperature of 170±5℃ and a drying time of 6h. After the material is dried, it is loaded into a sagger for sintering. The sintering conditions are heating to 350℃ at a heating rate of 5℃ / min, O2 concentration ≥95%, keeping warm for 8h, then cooling to 200℃ at 2℃ / min, and finally cooling to room temperature with the furnace to obtain a water-free high-nickel ternary positive electrode material.

[0089] Comparative Example 5

[0090] The difference between the water-free high-nickel ternary positive electrode material described in Comparative Example 5 and the water-free high-nickel ternary positive electrode material described in Example 3 is that the spray rates of the two solutions are both 1.2 L / min.

[0091] Comparative Example 6

[0092] The difference between the water-free high-nickel ternary positive electrode material described in Comparative Example 6 and the water-free high-nickel ternary positive electrode material described in Example 4 is that the concentration of Li2SiO3 is 2.4 mol / L, and the rest is the same as Example 4.

[0093] Comparative Example 7

[0094] The difference between the water-free high-nickel ternary positive electrode material described in Comparative Example 7 and the water-free high-nickel ternary positive electrode material described in Example 4 is that the amount of Li2SiO3 added is 15000 ppm, and the rest is the same as Example 4.

[0095] 1. Performance study of the water-free high-nickel ternary positive electrode material of the present invention:

[0096] 1.1 The BET of the positive electrode materials described in the examples and comparative examples of the present application was tested using the N2 adsorption method;

[0097] 1.2 Use a 25 ml measuring cylinder, an amplitude of 3 ± 0.2 cm, a frequency of 250 ± 15 times / min, and 5000 vibrations to test the tap density of the positive electrode materials described in the examples and comparative examples of the present application;

[0098] 1.3 After dissolving in water, the Li2CO3 content, LiOH content and free Li + content;

[0099] The test results are shown in Table 1:

[0100] Table 1 Performance study of the water-free high-nickel ternary positive electrode material described in this application

[0101]

[0102]

[0103] It can be seen from Table 1 that the surface coating by spraying can achieve the effect of coprecipitation coating. For example, the comparison between Example 5 and Comparative Example 3 shows that the difference between the two is not large. Since the solution is involved in the coprecipitation, some lithium ions will be dissolved into the solution, resulting in a slightly lower material capacity. From other comparative examples, it can be seen that the effect of spray coating one substance or dry coating is not as good as spray coating two substances. At the same time, there are certain requirements for the coating amount, spray rate and coating concentration. For example, in Comparative Examples 6 and 7, increasing the coating concentration and coating amount will greatly reduce the material capacity.

[0104] 2. The water-free high-nickel ternary positive electrode materials described in Examples 1-5 of the present application and the high-nickel positive electrode materials described in Comparative Examples 1-5 are mixed with SP and PVDF to prepare slurry, and the positive electrode material: SP: PVDF = 96.5%: 1.5%: 2%. A small coating machine is used to coat the positive electrode slurry on a 16 μm aluminum foil, and the surface density is controlled at 15-16 mg / cm 2 , after roller pressing, the compaction is controlled at 3.3g / cm 3 , cut the pole pieces according to the size requirements of 2430 button cells and assemble the batteries for testing. The test voltage range is 2.5-4.25V, the current is 0.1C, the capacity is the first week discharge capacity, and the first coulomb efficiency is the first discharge capacity / first charge capacity. The test results are shown in Table 2;

[0105] The water-free high-nickel ternary positive electrode materials described in Examples 1-5 of the present application and the high-nickel positive electrode materials described in Comparative Examples 1-5 are mixed with SP, KS-6, and PVDF to prepare slurry, and the positive electrode material: SP: KS-6: PVDF = 94.5%: 2%: 1%: 2.5% NMP is added to the mixture to prepare the positive electrode slurry, which is made into a positive electrode sheet through coating and rolling processes, and assembled with the negative electrode, separator, and electrolyte into a 503048 model battery. After 0.05C, 0.1C, and 0.2C formation, 1C capacity division is performed to obtain a testable battery cell with a capacity of about 800mAh. The capacity retention rate is calculated as the ratio of X-week capacity / first-week capacity, and the rate test method is 0.5C charging, 0.2C, 0.5C, 1C, and 2C discharge, and DCR test. At the specified SOC% state, 4C The 30S discharge recorded current value and the voltage difference before and after discharge, the ratio of the voltage difference to the discharge current is the DCR value under this SOC state, and the results are shown in Table 2.

[0106] Table 2

[0107]

[0108]

[0109] It can be seen from Table 2 that the rate performance and DCR performance of the material coated by water-free coating are better than those of dry coating and coating one substance, and its performance is equivalent to the wet co-precipitation coating performance, such as Example 5 and Comparative Example 3. However, since water-free coating produces almost no wastewater and does not require filter pressing, its cost is reduced. There are certain requirements for the spray rate, spray solution concentration and coating amount. Exceeding the range will cause the material performance to drop sharply. For example, in Comparative Example 5, although there is no obvious abnormality in its physical and chemical parameters after the spray rate increases, its rate, DCR and cycle performance deteriorate sharply, and the capacity of Comparative Examples 6 and 7 decreases sharply.

[0110] It can be seen from Table 2 that the DCR performance pattern of different SOC (State Of Charge) is that the DCR at 50% SOC is the smallest, the DCR at 10% SOC is the largest, and the DCR at 100% SOC is larger than that at 50% SOC. Comparative Examples 1 and 2 are dry-coated, with thick surface coating layers and large impedance, and therefore have greater impedance. Comparative Example 5 has a large spray rate, and the coating layer formed on the surface is relatively loose and thick, so the DCR is large.

[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A water-free high-nickel ternary positive electrode material, characterized in that: The molecular formula of the positive electrode material is: LiNi a Co b Mn c O2 / N, wherein 0.7≤a<1, 0<b<0.2, 0<c<0.2, a+b+c=1, N is a coating layer, and the coating layer is formed by one or more of SiO2, CoO2, Al2O3, ZrO2, SrO, Li3PO4, AlPO4, and the free Li of the positive electrode material + Content: Free Li + Content ≤2000ppm; The method for preparing the water-free high-nickel ternary positive electrode material comprises the following steps: (1) mixing the precursor and the lithium source uniformly and sintering at high temperature to obtain a sintered material; (2) spraying an alkaline solution containing Li+ on the surface of the calcined material obtained in step (1), and then spraying an acidic salt solution, and after spraying is completed, drying and sintering to obtain the water-free high-nickel ternary positive electrode material; The Li-containing + The alkaline solution is a LiAlO2 solution or a Li2SiO3 solution. + In alkaline solution, Li + The concentration of Li is 0.1-1 mol / L, and the spraying rate of the Li alkaline solution is 0.1-1 L / min; The acidic salt solution is Co(NO3)2, Zr(NO3)4, Zr(SO4)2, Sr(NO3)2, HF, LiF, LiH2PO4 or Al(H2PO3)3, the pH of the acidic salt solution is 1-6, and the spraying rate of the acidic salt solution is 0.1-1L / min; The Li-containing + The molar ratio of the spraying amount of the alkaline solution to the acidic salt solution is 0.1 to 5:1, and the Li-containing + The spray amount of the alkaline solution is 500 to 15000 ppm.

2. The water-free high-nickel ternary positive electrode material according to claim 1, characterized in that: The Li2CO3 content of the positive electrode material is: Li2CO3 content ≤ 500ppm, and the LiOH content of the positive electrode material is: 2000 ≤ LiOH content ≤ 5000ppm.

3. The water-free high-nickel ternary positive electrode material according to claim 1, characterized in that: The BET range of the positive electrode material is: 0.2~1.0m 2 / g, the tap density of the positive electrode material is: 2.3g / cm 3 ~3g / cm 3 .

4. The water-free high-nickel ternary positive electrode material according to claim 1, characterized in that: In step (1), the molecular formula of the precursor is: Ni a Co b Mn c (OH)2, wherein a≥0.7, and a+b+c=1; the lithium source is one or more of LiOH, Li2CO3, LiNO3, and CH3COOLi; the molar ratio of the precursor to the lithium source is 0.8-1.2:

1.

5. The water-free high-nickel ternary positive electrode material according to claim 1, characterized in that: In step (2), the drying is vacuum drying, and the sintering is firstly heating to 300-350°C at a heating rate of 1-10°C / min, keeping the temperature for 1-15h, then cooling to 180-220°C at a cooling rate of 1-3°C / min, and finally cooling to room temperature in the furnace.

6. A lithium battery, characterized in that: It comprises the water-free high-nickel ternary positive electrode material as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Water-washing-free coating method for high-nickel positive electrode material

    CN113809287A